KONSEP UANG DALAM PERSPEKTIF EKONOMI ISLAM - Ilyas, Rahmat (Universitas Islam Negeri Sunan Kudus, 2016)
Money is usability standards contained in the goods and labor.Money is defined as anything that is used to measure the typeof goods and labor. Suppose the price is standra for goods,while the wage is the standard for humans, each of which is anestimate of the value of goods and the power of people.Estimated values of goods and services wherever the land isrepresented by units, the units which is the standard used tomeasure the usefulness of goods and labor that became amedium of exchange (medium of exchange) and is called theunit of money In the Islamic concept, money is a flow concept.Islam does not recognize the motives need money because theydo not allow for speculation. Money is a good public,community property. Therefore, hoarding money is leftunproductive mean reducing the money supply.